2019
DOI: 10.1111/tct.12999
|View full text |Cite
|
Sign up to set email alerts
|

How can training in care of the dying be improved?

Abstract: Summary Background Care of the dying patient is an intrinsic part of the role of Foundation Year doctors (FYs). This study aimed to explore FYs’ experiences of training and their perceived training needs for their role in care of the dying. Methods All FYs in one Foundation school were invited to take part in semi‐structured group or individual interviews. A total of 8 group interviews and 21 individual interviews were conducted with 47 participants. Interview recordings were transcribed verbatim and framework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…All the papers provided evidence that the majority of junior doctors provide palliative and end-of-life care for many patients early in their careers 11–49. An average of 40% (range: 36%–46%) of junior doctors cared for 1–10 patients, while 51% (range: 40%–61%) of junior doctors cared for more than 10 patients 16 26 38 44…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the papers provided evidence that the majority of junior doctors provide palliative and end-of-life care for many patients early in their careers 11–49. An average of 40% (range: 36%–46%) of junior doctors cared for 1–10 patients, while 51% (range: 40%–61%) of junior doctors cared for more than 10 patients 16 26 38 44…”
Section: Resultsmentioning
confidence: 99%
“…Junior doctors’ personal attitudes towards palliative and end-of-life care varied. Many report a belief in the importance of palliation,14 17 20 21 24 34 37 41 44 45 47 48 some describing it as a privilege to care for patients at the end of their life 30 45. Some view palliative care as similar to other aspects of medicine, describing it as problem-solving patients’ symptoms 25 39 45.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have also found that clinical experience during clerkships has the greatest impact in improving student end-of-life care knowledge and competence [ 10 , 30 ]. Increased clinical exposure is positively correlated with increased confidence [ 31 , 32 ]. However, our respondents described isolated workshops that lacked strategy or cohesion and short-term rotations with limited clinical exposures to palliative patients.…”
Section: Discussionmentioning
confidence: 99%
“…The General Medical Council recommends that all medical students receive core teaching on care of the dying,2 3 however junior doctors continue to report distress and a lack of confidence when looking after the dying, often providing care in isolation and out of hours 4. As such, junior doctors often desire greater representation of palliative medicine teaching within undergraduate curricula 5…”
Section: Introductionmentioning
confidence: 99%